2013
DOI: 10.1371/journal.pone.0061947
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Culture Systems and 3, 5, 3'-Triiodothyronine/Follicle-Stimulating Hormone on Preantral Follicle Development in Mice

Abstract: The mechanical method to isolate preantral follicle has been reported for many years. However, the culture systems in vitro are still unstable. The aim of this study was to analyze the effect of the culture system of mice preantral follicles on the follicular development in vitro. The results showed that the 96-well plate system was the most effective method for mice follicle development in vitro (volume change: 51.71%; survival rate: 89%, at day 4). Follicle-stimulating hormone (FSH) and Thyroid hormone (TH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 59 publications
1
21
0
1
Order By: Relevance
“…An in vivo study using propylthiouracil-induced hypothyroid rats revealed that hypothyroidism may impact ovarian folliculogenesis, granulosa cell differentiation and steroidogenesis without affecting proliferation [22]. Thyroid hormone plays an important role in follicular development [23,24]. In addition, TSH directly suppressed follicle development in a concentration-dependent manner [25].…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo study using propylthiouracil-induced hypothyroid rats revealed that hypothyroidism may impact ovarian folliculogenesis, granulosa cell differentiation and steroidogenesis without affecting proliferation [22]. Thyroid hormone plays an important role in follicular development [23,24]. In addition, TSH directly suppressed follicle development in a concentration-dependent manner [25].…”
Section: Discussionmentioning
confidence: 99%
“…14, 15 Mehendale et al reported the follicle development suppression by TSH in a concentration dependent basis. 16 Though our study findings are well in support of previous findings, it has got some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Azaline B treatment also eliminates the surgical stress, which may adversely affect follicular functions in the long run, thus compromising follicular response to gonadotropins. Evidence suggests that T3 enhances follicular response to FSH leading to increased development of preantral follicles in mice (Zhang et al, 2013). T3 also prevents granulosa cell apoptosis following chemotherapy (Verga Falzacappa et al, 2012).…”
Section: Discussionmentioning
confidence: 99%